Surface-roughened current collectors for anode-free all-solid-state batteries - Gu Dong Hee; Kim, Hyoungchul; Lee, Jong Ho; Park, Sangbaek (Elsevier BV, 2022)
Anode-free all-solid-state batteries (AFASSBs), composed of a fully lithiated cathode and a bare current collector (CC) that eliminates excess lithium, can maximize the energy density (because of a compact cell configuration) and improve the safety of solid-state systems. Although significant progress has been made by modifying CCs in liquid-based anode-free batteries, the role of CCs and the mechanism of Li formation on CCs in AFASSBs are still unexplored. Here, we systematically investigate the effect of the surface roughness of the CCs on the Li plating/stripping behavior in AFASSBs. The results show that the moderately roughened CC substantially improves the Coulombic efficiency and cycle stability of AFASSBs owing to the increased contact points between the solid electrolyte and the roughened CC. In contrast, the excessively roughened CC deteriorates the performance owing to the contact loss. Moreover, an ex situ interface analysis reveals that the roughened surface of the CC could suppress the interfacial degradation during the Li ion extraction from a sulfide solid electrolyte to a CC. This provides an indication to the origin that hinders the electrochemical performance of AFASSBs. These findings show the potential for the application of surface-engineered CCs in AFASSBs and provide guidelines for designing advanced CCs. (C) 2022 Science Press and Dalian Institute of Chemical Physics, Chinese Academy of Sciences. Published by ELSEVIER B.V. and Science Press. All rights reserved.